KEDUDUKAN IZIN ISTRI DALAM POLIGAMI: Analisis Teori Perubahan Hukum dengan Perubahan Sosial - Harwis Alimuddin; Zulkarnain Abdurrahman (IAIN BONE, 2023)
Wife's permission for polygamy is not a requirement in classical fiqh. The Compilation of Islamic Law and the Marriage Law in Indonesia makes a previous wife's permission a condition for polygamy. Therefore, the wife's permission requirement is a condition resulting from the ijtihad process of Indonesian scholars which is adapted to the social and cultural structure in Indonesia. This research is expected to be a consideration for legal changes that support the principle of open monogamy in Indonesia. This study concludes that through an analysis of the theory of legal change with social change, even though the wife's permission in the classical period was not a requirement for polygamy, the wife's permission in the modern context must be used as a condition for polygamy permission. Changes in the social structure from a patriarchal culture that places the wife as the husband's subordinate to a social structure that places the wife as the husband's partner requires a change in the position permitted by the wife in polygamy. The wife's permission which is only used as a complementary requirement, an administrative requirement (min syurut al-kamal) can turn into a legal condition for polygamous marriage (min syurut al-sihhah).This is due to the consideration that polygamy which does not get the consent of the previous wife in the context of modern culture which places the wife as the husband's partner, can bring successive losses to the rights of the wife and children born from a polygamous marriage. Polygamy without the wife's permission causes it to be considered illegal by the state. The implication is that the interested parties will not be able to claim their rights in the future